FRI0620 MIR-204-3P inhibits the production of TLR4-related cytokines in familial mediterranean fever by targeting the PIK3 signaling pathway. (15th June 2017) - Koga, T; Migita, K; Umeda, M; Nonaka, F; Kawashiri, S-Y; Iwamoto, N; Ichinose, K; Tamai, M; Nakamura, H; Origuchi, T; Eguchi, K; Kawakami, A
Abstract : Background: MicroRNAs (miRNAs) are endogenous small RNAs and post-transcriptionally regulate gene expression by pairing with target. There has been emerging evidence showing the association of aberrantly expressed circulating miRNAs in the serum with the pathogenesis or progression of diseases including cancer and autoimmune disease. Although a number of circulating miRNAs associated with inflammation have been identified, the roles of them in patients with FMF and the underlying mechanism remain to be elucidated. Objectives: The aim of this study was to identify a serum miRNAs profile and potential biomarkers in FMF and clarify their gene targets for understanding the pathogenesis of autoinflammatory diseases. Methods: We performed miRNA microarray in the serum from FMF in attack and in remission. We subsequently examined the expression of miRNAs that varied before and after the attack in macrophages derived from THP-1 cells stimulated with toll-like receptor (TLR) ligands. Macrophages derived from THP-1 cells transfected with pre-miRNA and anti-miRNA were stimulated with TLR ligands for 24 hours. We collected the supernatants for the quantification of inflammatory cytokine production. To identify the target genes, we overexpressed its miRNA and performed Agilent expression microarray. Transfection with reporter construct and pre-miRNA and anti-miRNA was performed to confirm suppression of target mRNA. Results: We found that miR-204–3p was greatly decreased in the serum from FMF patients in attack. In vitro study, the expression of miR-204–3p was suppressed by LPS stimulation in macrophages derived from THP-1 cells. Inhibition of miR-204–3p significantly induced the production of TLR4-related cytokines whereas overexpression of miR-204–3p inhibited their production. Bioinformatic analysis showed that miR-204–3p is predicted to target genes implicated in TLR pathway through regulation of PIK3 signaling. Reporter assay revealed that miR-204–3p directly suppressed the luciferase activity of 3'UTR of PIK3CG reporter construct. Conclusions: These data suggest that serum miR-204–3p has a potential as a useful biomarker among patients with FMF and that miR-204–3p plays a critical role as a suppressor to regulate the production of TLR4 related cytokines by targeting PIK3 signaling pathway. Disclosure of Interest: None declared